Investigation of the proportions of some chemical components of two species of fish caught from the Drainage of AL- Haffar - kamil shatti, zahraa; Haidar Mashkoor Hussein (Al-Qadisiyah Journal of Pure Science, 2020)
This study is conducted during the period between October 2019 till July 2020 to measure the ratios of some chemical parameters in two species of fish prevalent in Al-Haffar Drainage. The concentrations of fats and proteins measured in three tissues (gills, skin, and muscles) of Tilapia Zilli and Liza Abu fish. The percentages of protein in Liza Abu fish were 14.41, 24.5, 14.47%, while in Tilapia Zilli were as: 14.6, 16.74, and 11.2% for gills, skin, and muscles separately. The levels of protein in tilapia were relatively higher, and the highest levels were recorded in the skin, while in Liza Abu, The highest rate of protein is noticing in the skin and muscles, Fat percentages in Liza. A fish were 1.33, 7.01, 2.09%, while in Tilapia.z f were 2.7, 5.19, and 2.3%, in gills, skin, and muscles, the highest fat ratio is registered in the skin of both species, The lowest levels of fat in Liza. A recorded in the gills, the lowest percentage of Fat in tilapia .z was recorded in muscles.